2021
DOI: 10.4018/978-1-7998-5567-5.ch011
|View full text |Cite
|
Sign up to set email alerts
|

Combating Fraud Through Forensic Accounting

Abstract: This study examines the potential application of forensic accounting in detecting and preventing of fraudulent activities in the administration of Islamic inheritance in Kano State, Nigeria. Data were collected through semi-structured interviews with some selected experts who are aware of Islamic inheritance and forensic accounting. Thematic analysis was used. The study established the nature and forms of the fraudulent activities committed in the administration of Islamic inheritance, such as non-compliance w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…However, the authors identified a few studies, such as Umar and Mohammed (2017), Umar and Kurawa (2019), and Umar and Haron (2021), that conceptually linked Islamic inheritance to accounting. Besides, Umar et al (2021b) empirically investigated the potential of forensic accounting to detect and prevent fraud in the administration of Islamic inheritance. Briefly, Islamic inheritance does not attract adequate attention from academics and practitioners of accounting.…”
Section: Introductionmentioning
confidence: 99%
“…However, the authors identified a few studies, such as Umar and Mohammed (2017), Umar and Kurawa (2019), and Umar and Haron (2021), that conceptually linked Islamic inheritance to accounting. Besides, Umar et al (2021b) empirically investigated the potential of forensic accounting to detect and prevent fraud in the administration of Islamic inheritance. Briefly, Islamic inheritance does not attract adequate attention from academics and practitioners of accounting.…”
Section: Introductionmentioning
confidence: 99%